2023
DOI: 10.1007/s11947-023-03208-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development on the Chemical Composition and Phenolic Extraction Methods of Apple (Malus domestica)—A Review

Marcellus Arnold,
Anna Gramza-Michalowska

Abstract: Apple (Malus domestica) is a reliable source of nutrients to increase the bioactive compounds intake in the human body. In the market, the development of apple is still growing, not only in the hybridization of new cultivars, but also in the functional food products, based on apple’s bioactive compounds. In this paper, we review the recent studies about the chemical composition of apples, including carbohydrates, proteins, lipids, dietary fibers, minerals, vitamins, phenolics, and other compounds, from various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…Asofei et al [30] reported an optimal MAE temperature of 90 • C for the extraction of polyphenols from SB leaves and a solvent/plant ratio of 20:1 and 50% ethanol as the extraction solvent. The two most fluctuating parameters in MAE are the microwave power and the extraction time which change depending on the plant species, BAMs, and various parts of the same plant [49]. Microwave power has considerable impact on the extraction of BAMs since microwave irradiation can speed the rupture of plant cells by rapidly raising the temperature and pressure [50].…”
Section: Effect Of Mae On the Tpc Of Sea Buckthorn Leaves And Berriesmentioning
confidence: 99%
“…Asofei et al [30] reported an optimal MAE temperature of 90 • C for the extraction of polyphenols from SB leaves and a solvent/plant ratio of 20:1 and 50% ethanol as the extraction solvent. The two most fluctuating parameters in MAE are the microwave power and the extraction time which change depending on the plant species, BAMs, and various parts of the same plant [49]. Microwave power has considerable impact on the extraction of BAMs since microwave irradiation can speed the rupture of plant cells by rapidly raising the temperature and pressure [50].…”
Section: Effect Of Mae On the Tpc Of Sea Buckthorn Leaves And Berriesmentioning
confidence: 99%
“…However, the main and characteristic components of each species are water, which occupies the largest percentage of the product (85.60 %), followed by sugars (13.8 %), proteins and lipids in smaller quantities, and dietary fiber, which is of interest to us, which amounts to about 2.40 g/100 g of product [19].…”
Section: Applementioning
confidence: 99%
“…Among the micronutrients, we can mention that apple is a good source of potassium (107 mg/100 g), β-carotene (27 mg/100 g) and other minerals and vitamins such as phosphorus, calcium, magnesium, vitamin C and B group and others [19].…”
Section: Applementioning
confidence: 99%
“…Among pectins, attention is drawn to apple pectin by processing apple pomace. A third of the world volume of apple pectin is produced in the USA, China, Brazil, Great Britain, Denmark, Italy, Germany, Austria, Bulgaria, and Poland [13][14][15].…”
Section: Introductionmentioning
confidence: 99%